Needs For Love And Belongingness In Maclachlan's Sarah, Plain And Tall Novel: A Humanistic Psychological Approach - ANSHORI, NASIR (2012)
The major problem of this study is Caleb who lost love and care from his mother because his mother died the day after Caleb was born. The objectives of the study are to analyze the novel based on its structural elements and to analyze the novel based on Humanistic Psychological Approach.. In analyzing Sarah Plain and Tall story the researcher uses qualitative method and Humanistic Psychological Approach. The object of the study is Patricia Maclachlan' Sarah Plain and Tall, published by Harper Collins Publisher Inc 2004. The data sources are primary data and secondary data. The primary data source is the novel Sarah Plain and Tall itself and the secondary data sources are the other sources related to the analysis such as the author's biography, the book of fiction, the book of psychoanalytic, dictionary, virtual references and the other relevant information that support this research. The method of data collection is library research by collecting and recording both of the primary and secondary data. The technique of data analysis used in this study is descriptive analysis. Based on the analysis above, the researcher draws the following conclusions: first, the researcher concludes that the elements of the novel present a good unity that consists of exposition, complication, climax, and resolution; second, Love and care of a mother are very needed by a child.